Does Fathers' Involvement in Childcare and Housework Affect Couples' Relationship Stability?*. (11th September 2018) - Norman, Helen; Elliot, Mark; Fagan, Colette
Abstract : Objective: Building on previous analysis conducted by Schober (2012), we explore how paternal involvement in different childcare and housework tasks affects the probability of relationship breakdown between parents. Methods: We use logistic regression on the U.K. Millennium Cohort Study to predict parental relationship breakdown from nine months to seven years post‐childbirth. Paternal involvement in four childcare and three housework tasks during the first year of parenthood, are used as explanatory variables. Results: The amount of time the father spends alone, caring for the baby during the first year of parenthood, is associated with the stability of the parental relationship but the effect of involvement in other tasks is moderated by ethnicity and the mother's employment status. Conclusion: These nonlinear relationships suggest further research is needed to explore the different associations between paternal involvement in childcare and housework and relationship breakdown, which are complex and variable according to different characteristics.